2015
DOI: 10.1111/2047-3095.12077
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Transition Theory‐Based Discharge Planning Program for Childhood Asthma Management

Abstract: Transition theory-based discharge planning program can guide nursing interventions to standardize care of the child with asthma. Combining care at home with hospital care strengthens ongoing qualified asthma management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 25 publications
2
41
0
3
Order By: Relevance
“…Four studies in which the effect of an inpatient parental education component on use was evaluated revealed reduced ED revisits. 27,37,53,63 Only 1 study (case-control) revealed that ED revisits increased with an educational intervention. 51 A reduction in ED revisits was revealed in both studies (RCTs) with contingency planning in the form of written care plans for home incorporated.…”
Section: Effects Of Family Engagement On Ed Revisitsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies in which the effect of an inpatient parental education component on use was evaluated revealed reduced ED revisits. 27,37,53,63 Only 1 study (case-control) revealed that ED revisits increased with an educational intervention. 51 A reduction in ED revisits was revealed in both studies (RCTs) with contingency planning in the form of written care plans for home incorporated.…”
Section: Effects Of Family Engagement On Ed Revisitsmentioning
confidence: 99%
“…Overall, CCIs were associated with reduced ED revisits in 52% of studies (9 of 17). Postdischarge follow-up care was associated with reduced ED revisits in 5 studies 27,35,53,77,91 (including 2 RCTs and 1 quasiexperimental study) but with increased ED revisits in 2 studies (including 1 casecontrol and 1 retrospective cohort study). 42,51 In regard to discharge planning, 3 studies in which a new person was hired to take responsibility for discharge planning or the existing care team was restructured to designate a responsible party for discharge planning revealed decreased ED revisits.…”
Section: Effects Of Care Coordination On Ed Revisitsmentioning
confidence: 99%
See 2 more Smart Citations
“…In patient training, multimedia technology has been widely used to increase understanding of suitable self-care activities to control disease symptoms such as diabetes (18,19), asthma (20), cancer (21), pregnancy (22), and colonoscopy (23). The effectiveness of multimedia technology in diabetic patients has been variable.…”
Section: Introductionmentioning
confidence: 99%